Antioxidant Vitamins, Calcium And Phosphorus Levels In Psoriasis - SREEKANTHA; MANJUNATHA GOUD B K; AVINASH S S; AMARESHWARA M; SUDHKAR; VINODCHANDRAN (International Journal of Pharma and Bio Sciences, 2010)
Psoriasis is regarded as a multifactorial disease in which interaction between genetic and environmental factors seem to play a causative role. Evidence is now accumulating that there is an association between Vitamin C, Vitamin E, Calcium, Phosphorus and psoriasis but the detailed mechanisms are not yet known. In the present study we estimated vitamin E, Vitamin C, Calcium and Phosphorus in 25 psoriatic patients and 25 age matched controls. We observed a very highly significant decrease in Vitamin E, Vitamin C and Calcium (p<0.001). It could be concluded from our study that decrease in above parameters are the probable causative agents for the pathogenesis of psoriasis.